Frequent PD-L1 Expression in Malignant Melanomas of the Vulva. (September 2018) - Saleh, Banafsheh; Kriegsmann, Jörg; Falk, Stephan; Aulmann, Sebastian
Abstract : Blockade of immune checkpoint pathways such as the programmed cell death protein 1 pathway (PD-1/PD-L1) is an emerging approach in the treatment of solid tumors. In malignant melanoma, the efficiacy of antibodies against PD-L1 has been shown to be associated with PD-L1 protein expression. To evaluate whether this approach may be of use in the rare cases of primary melanoma of the vulva, we have evaluated a series of 13 cases for PD-L1 expression as well as additional molecular alterations of KIT, NRAS, KRAS, and BRAF . PD-L1 expression was detected in 69% of cases and was not associated with any other molecular alteration, tumor stage or morphology. In conclusion, targeting PD-L1 by selective antibodies may be of benefit in the treatment of these uncommon tumors.